Analysis of the effects of microstructure heterogeneity on the mechanical behavior of additively manufactured Ti6Al4V using mechanics of structure genome. (June 2021) - Elkhateeb, Mohamed G.; Shin, Yung C.
Abstract: In this paper, the mechanics of structure genome (MSG) is introduced as a computationally efficient multiscale modeling approach to predict the effects of heterogeneous microstructure on the mechanical properties of AMed Ti6Al4V. Homogenization using MSG is conducted on a structure genome (SG) that incorporates the basic building details of the heterogeneous microstructure from the grain level and the modeling is carried out using the constitutive behaviors of the constituent phases with the evolution of microstructure without redoing homogenization. The microstructure-based MSG was employed to simulate the compression and tensile behaviors of AMed Ti6Al4V based on their microstructures. The predicted true stress-strain curves were then compared to the corresponding curves acquired from experimental testing. The simulation results matched well with the experimental results and showed the existence of martensite to be the reason behind the high strength in the AMed Ti6Al4V and the reduced ductility. Additionally, the inclusion of the microstructure in the SG allowed the MSG simulations to conform to the experiments in showing the reductions in the strengths and improvements in the maximum elongations in the AMed+heat treated Ti6Al4V due to grain coarsening and absence of martensite. Graphical abstract: Unlabelled Image Highlights: The mechanics of structure genome was used to predict the mechanical behavior of Ti6Al4V built by additive manufacturing. The structure genome included the basic representative heterogeneous microstructure of the fabricated parts. The MSG based simulations provided a very good agreement with the experiments in the mechanical behaviors. The MSG based method was computationally superior to RVE based simulations.